2001
DOI: 10.1891/0047-2220.32.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Members of Under-Represented Groups with Hearing Loss and VR Services: Explaining the Disparity in Closure Success Rates

Abstract: The purpose of this study was to explain, from a VR service perspective, reported differences in proportions of successful closures (i.e., status 26) based on race/ethnicity (Caucasians, African-American, American-Indian, Asian-American) and Hispanic origin (Latinos, non-Latinos) for persons who are deaf or hard of hearing. A series of cross tabulations and chi square analyses were utilized to investigate potential relationships between variables. Caucasians were found to achieve successful closure at a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…The result that consumers who received transportation services were 41% less likely to become competitively employed supports other outcome studies involving consumers with hearing loss (Moore, 2001c;Moore, 2002c). Transportation services did not significantly contribute to a predictive model of closure status for deaf and hard of hearing consumers (Moore, 2001c) or a predictive model of income at closure for consumers who were deaf (Moore, 2002c). No previous studies were found in which information and referral services contributed to a model predicting competitive employment.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The result that consumers who received transportation services were 41% less likely to become competitively employed supports other outcome studies involving consumers with hearing loss (Moore, 2001c;Moore, 2002c). Transportation services did not significantly contribute to a predictive model of closure status for deaf and hard of hearing consumers (Moore, 2001c) or a predictive model of income at closure for consumers who were deaf (Moore, 2002c). No previous studies were found in which information and referral services contributed to a model predicting competitive employment.…”
Section: Discussionsupporting
confidence: 72%
“…The extent to which VR services are effective on closure success for VR consumers with hearing impairments has been investigated by Moore (2001bMoore ( , 2001cMoore ( , 2002aMoore ( , 2002c using the data from the RSA-911 database. Moore (2001b) concluded that deaf and hard of hearing consumers are more likely to become competitively employed after receiving postsecondary education, on-the-job training, and job placement services than are deaf and hard of hearing consumers who did not receive these VR services.…”
mentioning
confidence: 99%
“…These services (counseling and guidance, job placement) historically have assisted individuals with disabilities in achieving successful employment (Status 26) and obtaining higher income levels. Although the VR program has been mandated to ensure equal access to effective services, an abundance of empirical evidence exists that suggests a disparity in successful rehabilitation outcomes for individuals based on gender (Danek & Lawrence, 1984;Harrison & Wayne, 1986;Wheaton, Wilson, & Brown, 1996), race/ ethnicity (Dzeikan & Okocha, 1993;Feist-Price, 1995;Moore, 2001), and types of services provided (Fraser & Shirley, 1986;Moore, Flowers, & Taylor, 2000;Zandy & James, 1979).…”
mentioning
confidence: 99%
“…Over the past several decades, a number of studies (Bolton, 1975;Lafitte, 1978;Moore, 2001;Watson, 1972) have focused on many of the aforementioned consumer and/or outcome variables for persons who are deaf. For example, Bolton reported that gender, race, and age were significant predictors of closure success.…”
mentioning
confidence: 99%
See 1 more Smart Citation